2024
DOI: 10.3390/neurolint16010010
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Axial Cavernous Angioma: A Case Report and Review of the Literature

Shakiba Hassanzadeh,
Linlin Gao,
Anthony M. Alvarado
et al.

Abstract: Cavernous angiomas (CAs) are benign vascular malformations predominantly seen in the brain parenchyma and therefore referred to as intra-axial. Extra-axial dural-based cavernous angiomas, on the other hand, are rare vascular lesions found outside of the brain parenchyma. They occur in the middle fossa and may be easily misdiagnosed as meningiomas due to their extra-axial location. In addition, CAs that are located outside the middle fossa, such as in the convexity, have a better prognosis since they are more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 90 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…In a recent review by Hassanzadeh et al, 91 extra-axial cavernous malformations were identified in the literature dating from 1947 to the present. 3 Of these, 11 were located on the tentorium. This figure corresponds to 12% of the reported cases ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent review by Hassanzadeh et al, 91 extra-axial cavernous malformations were identified in the literature dating from 1947 to the present. 3 Of these, 11 were located on the tentorium. This figure corresponds to 12% of the reported cases ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Focal neurological deficits and seizures have been reported in the literature. 3 The exact rate of hemorrhage is unknown, with the reported 9% risk for hemorrhage possibly overestimated, as the natural history is based largely on intra-axial cavernous malformations. 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations